Enhancing Innovation Performance in the Hotel Industry: The Role of Employee Empowerment and Quality Management Practices - Samer M. Al-Sabi; Mukhles M. Al-Ababneh; Mousa A. Masadeh; Ibrahim A. Elshaer (Administrative Sciences, 2023)
This research investigates employee empowerment’s role in the relationship between quality management practices (QMPs) and innovation performance at five-star hotels in Jordan. A total of 400 workers who work in five-star hotels in Jordan were given a questionnaire with 29 questions that measured QMPs, employee empowerment, and innovation performance. The obtained data were analyzed by PLS-SEM. The results show that quality policy (QP) has an insignificant influence on employee empowerment and innovation performance, while quality commitment (QC) and quality education and training (QET) have a positive and significant influence on employee empowerment and innovation performance. The results also reveal that employee empowerment has a positive influence on innovation performance. Finally, employee empowerment as a mediator variable was not working on the relationship between QP and innovation performance but showed a significant role as a partial mediator between QC and innovation performance as well as QET and innovation performance. Discussion, theoretical and managerial implications for future research, and limitations are presented.